Investigation of hydration and distribution of trifluoroacetophenone and its derivatives in hexane – aqua system - Matveichuk, Yulya V. (Journal of the Belarusian State University. Chemistry, 2019)
UV spectrophotometric and chromatographic study of the distribution and hydration of trifluoroacetophenone (TFAF) and some its derivatives ( p-trifluoroacetyl benzoic acid heptyl ester (TFABAHE), p-methyltrifluoroacetophenone ( p-MTFAF), 2,4-dimethyltrifluoroacetophenone (DMTFAF), 2,4,6-trimethyltrifluoroacetophenone (TMTFAF)) in the hexane-water system, which models the polyvinyl chloride membrane of ion-selective electrodes was investigated. TFAF has a high solubility in water (distribution coefficient D is equal to 415) as compared with p-MTFAF, DMTFAF, TMTFAF and TFABAHE (D within 1360 –2700). Hydration occurs most strongly to TFABAHE and is especially strong in alkaline medium. It is established that p-MTFAF and TFABAHE form a crystalline hydrates.